Gamification in Education: Its Impact on Engagement, Motivation, and Learning Outcomes - Ukgoda, Hansika (Journal of educational technology development and exchange, 2025)
Gamification, integrating game design elements into educational contexts, has emerged as a promising strategy to enhance student engagement, motivation, and learning outcomes. This systematic review synthesizes findings from 41 peer-reviewed studies published between 2012 and 2023, offering a comprehensive overview of the current state of gamification in education. Following PRISMA guidelines, the review evaluates the effectiveness of gamification elements such as points, badges, and leaderboards. Key Findings indicate that while gamification can foster positive learning attitudes and competition, its effectiveness depends on the context. The impact of game elements on engagement and motivation varies based on the learning environment and student characteristics. The review also highlights notable gaps in the literature, particularly around the long-term effects of gamification and the theoretical frameworks guiding its use. The implications of this research are twofold: first, it highlights effective practices for educators seeking to implement gamification strategies; second, it underscores the need for further investigation into the challenges associated with gamification, including potential drawbacks such as diminished intrinsic motivation and issues of fairness. Overall, this review contributes valuable insights for educators, policymakers, and researchers aiming to optimize gamified learning environments and enhance educational outcomes.